Does the functional polymorphism-1562C/T of MMP-9 gene influence brain disorders? - Pabian-Jewuła, Sylwia; Rylski, Marcin (Frontiers in Cellular Neuroscience, 2023)
Metalloproteinase-9 (MMP-9) is one of the most strongly expressed matrix metalloproteinases (MMPs) in the brain. The MMP-9 activity in the brain is strictly regulated, and any disruptions in this regulation contribute to a development of many disorders of the nervous system including multiple sclerosis, brain strokes, neurodegenerative disorders, brain tumours, schizophrenia or Guillain-Barré syndrome. This article discusses a relationship between development of the nervous system diseases and the functional single nucleotide polymorphism (SNP) at position -1562C/T within the MMP-9 gene. A pathogenic influence of MMP-9-1562C/T SNP was observed both in neurological and in psychiatric disorders. The presence of the allele T often increases activity of the MMP-9 gene promoter and consequently expression of MMP-9 when compared to the allele C. This leads to a change in the likelihood of an occurrence and modifies the course of certain brain diseases in humans, as discussed below. The presented data indicates that the MMP-9-1562C/T functional polymorphism influences the course of many neuropsychiatric disorders in humans suggesting a significant pathological role of the MMP-9 metalloproteinase in pathologies of the human central nervous system.